Meningkatkan Keterampilan Motorik Halus Anak Usia Dini Melalui Kegiatan Melipat (Origami) Pada Anak Kelompok A TK Aisyiyah Bustanul Athfal 06 Mojosari - TIA PRATAMA NINGTYAS (Universitas Muhammadiyah Surabaya, 2017)
Folding activities is one of the children's fine motor development activities. Folding activities required patience and thoroughness of the child. For that required appropriate learning strategies for learning objectives can be achieved as expected. This study aims to improve children's fine motor skills through folding activities. This study used classroom action research. Research subjects were 26 children of group A. The object of this study was fine motor skills through the folding activities (origami) in children group A. The method used in collecting data is observation, while the technical data analysis used qualitatively. Based on the results of research conducted in the folding activity of group A in TK Aisyiyah Bustanul Athfal 06 Mojosari obtained results from 26 children recorded as many as 6 children (26.07%) who had been able to fold well and the remaining 20 children (73.03%) Still having difficulty of folding instruction that conforms to the rules. From the research result, that the activity of children has increased score 20,03% from early data of first cycle equal to 68,07% and second cycle equal to 87,05%. While the activity of teachers has increased the score by 25% from the first 60% of the first cycle data and the second cycle by 85%. Keywords : Fine motor skill, origami